The Religious Identity of Banatian Bulgarians – The Palćans, in Serbia, Romania and Bulgaria - Vasić, Slobodan (Etnoantropolos̆ki problemi, 2022)
The paper presents a comparative study of religious identity in countries that share similar sociopolitical circumstances, namely socialism/communism and postsocialism. The analysis is based on field research, and the chosen subject of study is the ethnic group of Banatian Bulgarians, whose members live on the territory of Serbia, Romania and Bulgaria. The paper suggests that different regulatory practices by governments have had different effects on religious identity, and that other social factors, such as the size of the communities and language use, are also significant. Religion in the socialist/communist period was most strictly regulated in Bulgaria, where religious tradition was disrupted, while in Serbia the traditional component of religious identity was preserved in the private sphere, and in Romania secularization was present in some social strata. In postsocialism religion has been revitalized, and data suggest that a high level of religiousness is related to the ability to use one’s first language in church, which, in our study, is the case in Romania.